The context-dependent nature of the gendering of technical work : a case study of work in a scientific laboratory - Packer, Kathryn [Verfasser] (My University, 1996)
"This paper looks at the context-dependent nature of the gendering of technology. The case study reported on explores the relationship between scientists and machines - both inside and outside - the laboratory, and considers how this affects the gender division of labour in the company conderned. The stereotypical view, of women as technophonic and men as technophilic, is challenged. However, the results show how the dominant masculinised discourse around technology is implicated in the under-representation of women in senior positions. The paper argues that, in addition to structural analysis of occupationale segregation, an understanding of the dynamics of gender symbolism and identity also need to be incorporated into the debate." (author's abstract, IAB-Doku) ((en)) Im Rahmen einer Fallstudie wird gechlechtsspezifischer Umgang mit Technik untersucht. Wissenschafltiche Mitarbeiter eines Labors wurden nach ihrer Techniknutzung am Arbeitsplatz und in der Freizeit befragt. Die stereotype Ansicht einer weiblichen Abneigung gegen Technik wird in Frage gestellt. Allerdings zeigt sich eine Unterrepräsentanz von Frauen in Aufstiegspositionen. (IAB)
Keywords: S 6.3.1 Ingenieurberufe, Chemiker, Physiker, Mathematiker; G 1.2 Arbeitsmarkt; P 1.3 Frauen; S 6.4 Dienstleistungsberufe; G 2.4.1 Bildungs- und Berufswege; G 2.4.4 Biografiegestaltung; I 2.2.1 Westeuropa; Chemiker; Arbeitsmarktsegmentation; Geschlechtsspezifische Faktoren; Frauen in Einzelberufen; Frauenarbeit; Technik; Anwendung; Wissenschaftler; Frauen; Freizeit; Beruflicher Aufstieg; Berufsproblem; Großbritannien